PENAMBAHAN VITAMIN C PADA PAKAN BUATAN TERHADAP PERTUMBUHAN BENIH IKAN GABUS (Channa striata) - Alfisha, Tisie Hawa; Syakirin, M. Bahrus; Mardiana, Tri Yusufi; Linayati, Linayati; Madusari, Benny Diah (JURNAL LITBANG KOTA PEKALONGAN, 2020)
The purpose of this study was to determine the effect of adding vitamin C in artificial feed and the optimum dose to the growth of snakehead fish seeds. The research method used was a completely randomized design with 4 treatments and 3 replications. The treatments used were: A (giving vitamin C at a dose of 50 mg/kg of feed), B (giving vitamin C at a dose of 100 mg/kg of feed), C (giving vitamin C at a dose of 150 mg/kg of feed), D ( giving vitamin C at a dose of 200 mg/kg of feed). The results showed that the highest average biomass growth was obtained in treatment D with a dose of vitamin C 200 mg/kg of feed, the increase in biomass reached 3.04 grams. While the lowest growth was obtained in treatment A with a dose of vitamin C 50 mg/kg of feed resulting in an average growth of 1.09 grams. The results of the analysis of variance on the growth of snakehead fish seed biomass showed that the calculated F value was greater than F table 1% and 5%. The range of water temperature during the study was between 27 -30 o C, water pH ranged from 7.4-7.6 and dissolved oxygen in water (DO) ranged from 4.2-4.9 mg/l. Keywords: snakehead , vitamin C, growth